Electromagnetic shielding and electrical properties of polyurethane acrylate/E-glass composites in the 3-13 GHz frequency range - (:unkn) unknown (My University, 2011)
The electromagnetic shielding effectiveness (EMSE) and surface resistivity of UV-cured polyurethane acrylate (PUA)/copper wire/E-glass fabric composites in the frequency range of 3-13 GHz were investigated using a free space measurement. The effect of polyvinyl butyral (PVB) binder on the shielding and electrical properties were searched by using a range of PVB concentrations 2.5, 5, 7.5 % and without PVB. The best EMSE value of 25 dB was obtained in the frequency range of 5-9 GHz by adding 2.5 % PVB. When the addition of PVB was more than 2.5 %, the shielding effect decreased. The sample which contains 2.5 % PVB was showed the least surface resistivity and the best EMSE value. © 2011 IEEE.